Product market imperfections and employment dynamics - Mikael Carlsson; Stefan Eriksson; Nils Gottfries (Uppsala University, Department of Economics, 2011)
How important is imperfect competition in the product market for employment dynamics? To investigate this, we formulate a theoretical model of employment adjustment with imperfect competition in the product market, search frictions, and convex adjustment costs. From this model, we derive a structural equation for employment that we estimate on firm-level data. We find that product market demand shocks have significant and quantitatively large effects on employment. Thus, product market imperfections seem to be important for employment dynamics. However, we find no evidence that the tightness of the local labor market affects job creation in existing firms.
Keywords: E24; J23; J64; 330; Search-Matching; Job Creation; Unemployment; Labor Demand